Structure of foreign investment in the industry of Poland at the beginning of the second decade of the 21st century - Tobolska Anna (Bulletin of Geography. Socio-Economic Series)
This paper seeks to analyse the sectional and spatial structure of the inflow of foreign direct investment (FDI) to industry in Poland and to determine the extent of internationalisation of this sphere of the economy. Those issues are significant not only in cognitive terms, but can also have implications for the country’s economy, in particular for its economic policy. In the first step of the research procedure an analysis was characterised the structure of foreign investment in the various sectors of industry was on the basis of selected variables: the capital invested, the number of companies with foreign capital, and the employment generated. To assess differences in the divisional structure, use was made of two quantitative methods: Rodgers’ relativised index of structure diversification and Creamer’s diversification index. Then the spatial structure of the foreign capital inflow to Polish industry was identified in two aspects: by region where investment was located and by the investors’ country of origin. On the basis of the observed tendencies and regularities, an assessment was made of foreign direct investment in Polish industry, and the performed analysis was summed up by constructing an FDI internationalisation profile. In the paper use was made of statistical data obtained from the following sources: reports published by the National Bank of Poland; information and materials published by the Central Statistical Office (GUS); and information and materials published by the Polish Information and Foreign Investment Agency (PAIiIZ).